2018
DOI: 10.3390/s18072387
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Optimal Heart Rate Variability Features Based on SVM-Recursive Feature Elimination for Cumulative Stress Monitoring Using ECG Sensor

Abstract: Routine stress monitoring in daily life can predict potentially serious health impacts. Effective stress monitoring in medical and healthcare fields is dependent upon accurate determination of stress-related features. In this study, we determined the optimal stress-related features for effective monitoring of cumulative stress. We first investigated the effects of short- and long-term stress on various heart rate variability (HRV) features using a rodent model. Subsequently, we determined an optimal HRV featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…Feature selection was performed on the MRI data of brain tissue, and the classification using USVM-RFE showed better results than the one using SVR-RFE. The implementation of RFE was also done in the study [18], where RFE-SVM was used to determine the best feature among the various heart rate variability (HRV) data. The study showed that RFE-SVM could identify the HRV feature and detect the stress level better.…”
Section: Related Workmentioning
confidence: 99%
“…Feature selection was performed on the MRI data of brain tissue, and the classification using USVM-RFE showed better results than the one using SVR-RFE. The implementation of RFE was also done in the study [18], where RFE-SVM was used to determine the best feature among the various heart rate variability (HRV) data. The study showed that RFE-SVM could identify the HRV feature and detect the stress level better.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, a master feature vector is created and GridSearch-based Recursive Feature Elimination with Cross-validation (RFECV) scheme followed by stacked generalization is introduced to select, rank, extract suitable feature subset with higher classification prediction performance with reduced generalization errors. RFECV and stacked generalization have previously been proven best in various related application domains [25,26].…”
Section: Related Workmentioning
confidence: 99%
“…Recursive Feature Elimination (RFE) is a scheme that excludes features based on its irrelevancy and low data integrity to a specified class distribution [25,35]. The elimination process is a continuous process until a complete list of deterministic feature subset is reached.…”
Section: Gridsearch-based Rfecv + Ig Feature Selection Schemementioning
confidence: 99%
“…Lanata [41] used this algorithm to identify horses' response to human fear and happiness. Mirhoseini [42] used it to detect early cardiac death while this pattern recognition classifier was also used for health care applications based on Heart Rate Variability [45][46][47][48][49][50] The main use of this supervised algorithm is to distinguish between two classes (or more). Having a set of points in a feature space, each point is associated to a label.…”
Section: Support Vector Machinementioning
confidence: 99%